2015
DOI: 10.3906/bot-1406-84
|View full text |Cite
|
Sign up to set email alerts
|

Foliar spray of phyto-extracts supplemented with silicon: an efficacious strategy to alleviate the salinity-induced deleterious effects in pea (Pisum sativum L.)

Abstract: IntroductionAbiotic stresses drastically affect crops by minimizing yield. Plants face many distinctive abiotic stresses at different stages of plant growth and development. Among these stresses, salinity is prejudicious, limiting plant growth and productivity. Salt stress causes various deleterious effects on morphological, physiological, biochemical, and nutritional attributes. The formation of reactive oxygen species (ROS) is the significant consequence of salt stress. The major ROS comprise hydroxyl ( . OH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 35 publications
(34 reference statements)
3
25
0
Order By: Relevance
“…Piper-derived extracts demonstrated strong potential for mitigating insect pests [27][28][29]. The efficacy of the locally produced dual-purpose organic amendment is consistent with reports where Piper extract was effective as contact botanical insecticides in reducing insect pest damage, even when combined with garlic or lemon grass oil [28,48].…”
Section: Impact Of Treatments On Tomato Damage By Mole Cricketsupporting
confidence: 74%
See 2 more Smart Citations
“…Piper-derived extracts demonstrated strong potential for mitigating insect pests [27][28][29]. The efficacy of the locally produced dual-purpose organic amendment is consistent with reports where Piper extract was effective as contact botanical insecticides in reducing insect pest damage, even when combined with garlic or lemon grass oil [28,48].…”
Section: Impact Of Treatments On Tomato Damage By Mole Cricketsupporting
confidence: 74%
“…alkaloids, flavonoids, phenolic, etc.) with insecticidal and antifungal potentials for mitigating insect pests and diseases [27,29].…”
Section: Impact Of Treatments On Tomato Damage By Mole Cricketmentioning
confidence: 99%
See 1 more Smart Citation
“…Application of silicon decreased activities of antioxidant enzymes under salinity stress; this is associated with decreasing of electrolyte leakage, ROS synthesis and H 2 O 2 contents (Siddiqui et al, 2014 andShahid et al, 2015). More or fewer data were reported by Abbas et al (2015) that foliar application of silicon (150 mgL −1 ), decreased lipid peroxidation and increased antioxidant enzymes activities in both leaves and root of okra under salt stress.Similar studies showed that siliconmediated enhancement in antioxidant enzyme activities and decreased in oxidative stress in saltstressed tomato plants grown in sand culture (Li et al, 2015).…”
Section: Antioxidant Defense Systemmentioning
confidence: 99%
“…These substances possess synergistic effects on retarding growth of pests and suppression of pathogens hence act as insecticidal and antifungal agents (Ahmed et al, 2012). Plant extracts have been successfully applied against insect pests and diseases (Shahid et al, 2015). In Kenya formulated products of neem and pyrethrum are currently used whereas a mixture of garlic and pepper has been recommended to manage insect pests (Infonet-Biovision, 2015;Ogala, 2013).…”
Section: Introductionmentioning
confidence: 99%